Vaccine hesitancy - a potential threat to the achievements of vaccination programmes in Africa - Sara Cooper; Cornelia Betsch; Evanson Z. Sambala; Nosicelo Mchiza; Charles S. Wiysonge (Taylor & Francis Group, 2018)
Vaccination programmes in Africa have made extraordinary progress over the last four decades. Yet, vaccine hesitancy threatens to erode these gains. Vaccine hesitancy is a continuum between vaccine acceptance and refusal. A growing number of people in Africa are delaying or refusing recommended vaccines for themselves or their children, even when safe and effective vaccines are available. This predisposes communities to infectious diseases, resulting in multiple disease outbreaks, ultimately consuming resources and costing lives. Vaccine hesitancy is currently receiving unprecedented global attention, however, there remains several knowledge gaps, particularly in Africa. The vast majority of research on this topic has been conducted in high income countries. Little is therefore known about the nature and causes of vaccine hesitancy in Africa, and evidence-based interventions in the region to address it are also limited. Moreover, tools to measure vaccine hesitancy are scarce, and none that exist have been validated in Africa. We discuss these knowledge gaps, and propose a research and capacity building agenda to better measure and overcome vaccine hesitancy in Africa. Ultimately, this is essential if we hope to enhance and sustain public demand for vaccination and preserve the tremendous achievements of vaccination programmes on the continent.